2020
DOI: 10.2147/lra.s272694
|View full text |Cite
|
Sign up to set email alerts
|

<p>Interfascial Plane Blocks and Laparoscopic Abdominal Surgery: A Narrative Review</p>

Abstract: Laparoscopic abdominal surgery has become a mainstay of modern surgical practice. Postoperative analgesia is an integral component of recovery following laparoscopic abdominal surgery and may be improved by regional anesthesia or intravenous lidocaine infusion. There is inconsistent evidence supporting the use of interfascial plane blocks, such as transversus abdominis plane (TAP) blocks, for patients undergoing laparoscopic abdominal surgery as evidenced by variable patterns of local anesthetic spread and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 94 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…QLBs have been part of our daily practice for over a decade, and many studies have shown their analgesic efficacy for different abdominal procedures. [16][17][18] However, concerns regarding coagulopathy and metabolism disturbances limit the application of QLBs in pediatric transplant surgeries. 11,12,16,19 Our study showed good postoperative pain control and decreased opioid consumption in the kidney transplant group and early extubation, short ICU and hospital stay, and a low complication rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QLBs have been part of our daily practice for over a decade, and many studies have shown their analgesic efficacy for different abdominal procedures. [16][17][18] However, concerns regarding coagulopathy and metabolism disturbances limit the application of QLBs in pediatric transplant surgeries. 11,12,16,19 Our study showed good postoperative pain control and decreased opioid consumption in the kidney transplant group and early extubation, short ICU and hospital stay, and a low complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first pediatric retrospective study analyzing the use of QLBs for perioperative pain management after abdominal transplant surgery in children. QLBs have been part of our daily practice for over a decade, and many studies have shown their analgesic efficacy for different abdominal procedures 16–18 . However, concerns regarding coagulopathy and metabolism disturbances limit the application of QLBs in pediatric transplant surgeries 11,12,16,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, newer interventional modalities, such as QL and ESP blocks, have been proposed as good alternatives since they potentially provide somatic and visceral analgesia. However, current evidence has not shown clear benefits of using these techniques when compared to TAP blocks [75,76]. Further clarification is needed to determine the role of these techniques in abdominal surgery and ERAS protocols.…”
Section: Abdominal and Pelvic Surgerymentioning
confidence: 99%
“…Laparoscopic abdominal surgery has become a mainstay of modern surgery with reduced surgical stress and postoperative pain. Evidence promotes thoracic erector spinae (T-ESP) block (T7-9) for laparoscopic abdominal surgery in particular from studies investigating pain following laparoscopic cholecystectomy (LC) [ 1 , 2 ]. The ESP block first described by Forero et al in 2016 [ 3 ] has been shown to be useful in many surgeries.…”
Section: Introductionmentioning
confidence: 99%